Outcomes of 1000 Carotid Wallstent Implantations: Single-Center Experience. (April 2016) - Ronchey, Sonia; Praquin, Barbara; Orrico, Matteo; Serrao, Eugenia; Ciceroni, Cristina; Alberti, Vittorio; Fazzini, Stefano; Mangialardi, Nicola
Purpose: To evaluate the outcomes of carotid artery stenting (CAS) with Wallstents in a single-center experience.Methods: From January 2003 to December 2013, 1000 carotid artery lesions were treated with Carotid Wallstents under cerebral protection in 877 patients (mean age 71.7±8 years; 621 men). Indications for treatment were de novo lesions (>70% asymptomatic and >60% symptomatic); stenoses following carotid endarterectomy, radiation, or neck surgery; contralateral laryngeal nerve palsy; and high surgical risk. All the patients underwent duplex ultrasound and clinical evaluation during follow-up; radiography was performed when fracture or stent migration was suggested by ultrasound.Results: Procedure success was achieved in 99.3% of patients. Major and minor 30-day adverse events occurred in 2.1% of patients, including stroke (1.8%: 1.3% minor, 0.5% major), myocardial infarction (0.1%), and death (0.2%). Plaque morphology, nature of stenosis, and symptomatic status were significantly associated with the risk of postoperative neurologic events. Restenosis occurred in 3.2% at a mean 45.5-month follow-up and was significantly associated with diabetes, smoking, symptomatic stenosis, de novo stenosis, and calcification (plaque III/IV). No fracture or migration was registered during follow-up.Conclusion: CAS is a valid method for treating carotid artery disease, with very low rates of major adverse events and neurologic complications. The Carotid Wallstent seems to have excellent results, even with complex plaque morphology, and a low incidence of restenosis at follow-up.